Join IDNLearn.com today and start getting the answers you've been searching for. Find the information you need quickly and easily with our comprehensive and accurate Q&A platform.
Sagot :
[tex]9x^2-4y^2-24y-72=0\\
\\
9x^2-4y^2-24y=72\\
\\
9x^2-(4y^2+24y+36)=72-36\\
\\
9x^2-4(y+3)^2=36\\
\\
\frac{9x^2}{36}-\frac{4(y+3)^2}{36}=\frac{36}{36}\\
\\
\boxed{\frac{x^2}{4}-\frac{(y+3)^2}{9}=1}[/tex]
Your participation is crucial to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. Your search for solutions ends at IDNLearn.com. Thank you for visiting, and we look forward to helping you again.